Effects of prophylactic antibiotic administration and antibiotic timing on culture results and clinical outcomes of paediatric musculoskeletal infection: a protocol for a randomised controlled clinical trial - Chao You; Yibiao Zhou; Zhiyong Liu; Chao Deng; Yongjie Xia; Dechao Wu; Liangfu Xie; Bing E; Jingming Han (BMJ Open)
Introduction Musculoskeletal infection (MSI) is a common cause of morbidity among the paediatric population. Some clinicians recommend withholding prophylactic antibiotics until culture collection with an aim to improve the culture sensitivity. However, a recent retrospective study reported that prophylactic antibiotic administration did not affect culture sensitivities in either disseminated or local MSI in paediatric population, which is surprising. The aim of the present study is to investigate the effects of prophylactic antibiotic administration and the timing of antibiotic administration on culture sensitivity and clinical outcomes of paediatric MSI.Methods and analysis A randomised controlled clinical trial will be carried out. Individuals aged 0–18 years with a diagnosis of MSI will be screened and evaluated at the Shenzhen Children’s Hospital. The participants will be randomly allocated into four groups, and they will receive the antibiotic treatment at different time points, that is, 1 week, 3 days, 1 day prior to tissue culture collection and 1 day after tissue culture collection, respectively. The primary outcome will be culture sensitivity. In addition, the disease-related markers including white blood cell count, C reactive protein, erythrocyte sedimentation rate, vital signs as well as the length of hospital stay will be measured or recorded accordingly. Using χ2 tests, the rates of positive cultures will be compared between different groups. Statistical comparisons between the different patient groups regarding the confounding and outcome variables will be conducted using independent t-tests, Mann-Whitney U tests, χ2 tests and Fisher’s exact tests as appropriate with the significance level set to 5% (p<0.05).Ethics and dissemination This study has received ethical approval. The findings will be disseminated both in scientific conferences and peer-reviewed journal.Trial registration number ChiCTR2100041631.